Plasma lipidome, circulating inflammatory proteins, and Parkinson’s disease: a Mendelian randomization study - Qin, Yidan; Wang, Lin; Song, Jia; Quan, Wei; Xu, Jing; Chen, Jiajun (Frontiers in Aging Neuroscience, 2024)
Background：Observational studies have suggested that plasma lipidome play a pivotal role in the occurrence of Parkinson's disease (PD). However, clarity is lacking regarding the causal relationship between plasma lipidome and PD, as well as whether circulating inflammatory proteins serve as mediators.Methods：Single nucleotide polymorphisms (SNPs) significantly associated with 179 plasma lipidome were selected as instrumental variables to assess their causal impact on PD. Heterogeneity, pleiotropy tests, and reverse causality analyses were conducted accordingly. Additionally, we analyzed the causal relationship between 91 circulating inflammatory proteins and PD, exploring whether these proteins serve as mediators in the pathway from plasma lipidome to PD. Results：Among the 179 plasma lipidome, three were found to be associated with a reduced risk of PD: Phosphatidylcholine (14:0_18:2) (IVW, OR=0.877; 95%CI, 0.787-0.978; p=0.018), Phosphatidylcholine (16:0_16:1) levels (IVW, OR=0.835; 95%CI, 0.717-0.973; p=0.021), and Phosphatidylcholine (O-17:0_17:1) levels (IVW, OR=0.854; 95%CI, 0.779-0.936; p=0.001). Meanwhile, Sphingomyelin (d38:1) was linked to an increased risk of PD (IVW, OR=1.095; 95%CI, 1.027-1.166; p=0.005). Among the 91 circulating inflammatory proteins, three were associated with a lower PD risk: Fibroblast growth factor 21 levels (IVW, OR=0.817; 95%CI, 0.674-0.990; p=0.039), Transforming growth factor-alpha levels (IVW, OR=0.825; 95%CI, 0.683-0.998; p=0.048), and Tumor necrosis factor receptor superfamily member 9 levels (IVW, OR=0.846; 95%CI, 0.744-0.963; p=0.011). Two were associated with a higher risk of PD: Interleukin-17A levels (IVW, OR=1.285; 95%CI, 1.051-1.571; p=0.014) and TNF-beta levels (IVW, OR=1.088; 95%CI, 1.010-1.171; p=0.026). Additionally, a positive correlation was observed between Phosphatidylcholine (14:0_18:2) levels and Fibroblast growth factor 21 levels (IVW, OR=1.125; 95%CI, 1.006-1.257; p=0.038), suggesting that Fibroblast growth factor 21 levels may serve as a mediating factor in the pathway between Phosphatidylcholine (14:0_18:2) levels and PD. The mediation effect was estimated to be -0.024, accounting for approximately 18% of the total effect.Conclusion：Both plasma lipidome and circulating inflammatory proteins demonstrate a causal relationship with PD. Additionally, circulating inflammatory proteins may serve as mediators in the pathway from plasma lipidome to PD. These findings may contribute to the prediction and diagnosis of PD and potentially pave the way for targeted therapies in the future.